Role of peer influence and thin-ideal internalization on body dissatisfaction and disordered eating in mexican girls/ rol de la influencia de pares y de la interiorización del ideal de delgadez sobre la insatisfacción corporal y alimentación no... (2012)
The aim of this study was to examine the role of peer influence and thin-ideal internalization on body dissatisfaction and disordered eating. The Eating Attitudes Test, the Body Shape Questionnaire and the Questionnaire of Sociocultural Influences on the Aesthetic Body Shape Model were administered to 130 female students, with a mean age of 19.44. The results showed that thin-ideal internalization mediated the relationship between peer influence and body dissatisfaction (β=0.14, p and gt;.05), and the relationship between peer influence and disordered eating (β=0.09, p and gt;.05). This study supports the hypothesis that the thin-ideal internalization is an important mediator on body dissatisfaction and disordered eating in Mexican girls.